An Overview on Composite Sorbents Based on Polyelectrolytes Used in Advanced Wastewater Treatment - Florin Bucatariu (MDPI AG, 2021)
Advanced wastewater treatment processes are required to implement wastewater reuse in agriculture or industry, the efficient removal of targeted priority and emerging organic & inorganic pollutants being compulsory (due to their eco-toxicological and human health effects, bio-accumulative, and degradation characteristics). Various processes such as membrane separations, adsorption, advanced oxidation, filtration, disinfection may be used in combination with one or more conventional treatment stages, but technical and environmental criteria are important to assess their application. Natural and synthetic polyelectrolytes combined with some inorganic materials or other organic or inorganic polymers create new materials (composites) that are currently used in sorption of toxic pollutants. The recent developments on the synthesis and characterization of composites based on polyelectrolytes, divided according to their macroscopic shape—beads, core-shell, gels, nanofibers, membranes—are discussed, and a correlation of their actual structure and properties with the adsorption mechanisms and removal efficiencies of various pollutants in aqueous media (priority and emerging pollutants or other model pollutants) are presented.